Islamic Perspective on Adolescent Smoking Behaviour - Sutanto Priyo Hastono; Fatimah Fatimah; Triana Srisantyorini; Muhammad Farid Hamzens; Iswan Iswan (Indonesian Journal of Islam and Public Health, 2022)
Indonesia is the third country with the largest number of smokers in the world after China and India. An increase in cigarette consumption is associated with an increase in the burden of disease due to smoking and an increase in the death rate due to smoking. It is estimated that the mortality rate of smokers in the world will reach 10 million people and 70% of them will come from developing countries by 2030. The results of the Basic Health Research (Riskesdas) show that the increase in the prevalence of smoking in the population aged 10-18 years with the age of 10 years has increased from the original 28.8% in 2013 to 29.3% in 2018. The purpose of this study is to examine some of the literature on Islamic perspectives on adolescent smoking behavior. This study uses a literature review method where the researcher conducts a series of studies involving various kinds of information from the literature such as journals and theses. The results of research from various sources indicate that adolescents who smoke do not know the side effects of the dangers of smoking behavior. Because basically they just follow the association made by peers. As parents, educators (teachers) naturally contribute to solving deviant behavior in adolescents. Islam recommends several approaches in solving these problems, for example, inculcating religious values, education for children, personality formation and good advice (mau'izhah hasanah).